(untitled) (Journal of Organizational Psychology, 2017)
The goal of this study was to better understand the lived experiences, perceptions, and attitudes of nontraditional, adult university students enrolled in an online baccalaureate degree program, who were given an opportunity to participate in an engaged, study-abroad program. This understanding was achieved through rigorous analysis of student learning journals required as part of the course. Students were asked to journal their feelings, perceptions, experiences and learning. The purpose of the analysis was to identify and describe the various experiences and perceptions, then group these experiences and perceptions into a logically organized description of the lived experience of adult students.